STRAUSS, LEO, Liberalismo antiguo y moderno. - Pernas Alonso, José María (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
(Madrid, Katz Editores, 2007). 390 pp. ISBN 978-84-96859-15-9